The use of information and communication technology and the quest for accountability among political leaders and public office holders in local governance in Nigeria (Economic and Political Thought, 2022)
This study examines the relationship between ICT use and political leaders and public office holders’ accountability in the local  Southwestern Nigeria. In Southwestern Nigeria, there signifcantly appears to be little or no attempt to investigate the role of ICT usage and its impact on political leaders and public office holders’ accountability. At the same time, in considering this as the starting point for this topic, the study utilised primary data collected through a mixed approach method of surveying local council ICT officers, registered voters, local community and youth leaders, and key interviews with officers of ICT non-governmental organisations. In the quantitative design, 418 respondents were administered the questionnaire, and 18 key informants were purposefully interviewed. The data were analysed via SPSS; tables were utilised for correlation co-efficient analysis, and content analysis was used to present the interview responses. The results revealed a positive correlation of +0.576 between ICT use and political leaders and public office holders’ accountability in local governance. The study finds that using appropriate ICT tools in rural communities will improve local governance.
Keywords: ICT, local governance, accountability, e-governance and Southwestern Nigeria